2007
DOI: 10.1038/sj.ejcn.1602688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 12-week low glycaemic index diet on heart disease risk factors and 24 h glycaemic response in healthy middle-aged volunteers at risk of heart disease: a pilot study

Abstract: Objective: To compare the effects of two energy-restricted healthy diets, one with a low GI and one with a high GI, on heart disease risk factors and weight loss in subjects at risk of heart disease. Design: A 12-week randomized parallel study of low and high GI, healthy eating diets was carried out. Setting: The study was carried out at the Hammersmith Hospital. Subjects: Eighteen subjects were recruited by advertisement and randomized to one of the two diets. Fourteen completed the study but one was excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…However, this does not take into account that the metabolic response varies substantially between carbohydrates, as evidenced by different glycemic and insulinemic responses [3] . Diets that include carbohydrates with a low-glycemic response result in lower glucose and lipid levels when compared to high-glycemic diets [8,36,37] . While there are no long-term clinical trials examining the effects of high-or low-glycemic diets on insulin resistance or obesity in the elderly, two small clinical trials report greater weight loss utilizing a low-glycemic approach [8,38] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this does not take into account that the metabolic response varies substantially between carbohydrates, as evidenced by different glycemic and insulinemic responses [3] . Diets that include carbohydrates with a low-glycemic response result in lower glucose and lipid levels when compared to high-glycemic diets [8,36,37] . While there are no long-term clinical trials examining the effects of high-or low-glycemic diets on insulin resistance or obesity in the elderly, two small clinical trials report greater weight loss utilizing a low-glycemic approach [8,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Diets that include carbohydrates with a low-glycemic response result in lower glucose and lipid levels when compared to high-glycemic diets [8,36,37] . While there are no long-term clinical trials examining the effects of high-or low-glycemic diets on insulin resistance or obesity in the elderly, two small clinical trials report greater weight loss utilizing a low-glycemic approach [8,38] . Studies conducted by our group observed improvements in insulin and glucose metabolism in insulin-resistant cirrhotic patients after a low-glycemic diet [39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten randomised controlled trials were identified that presented evidence on GI in relation to fasting blood lipid concentration, all of which were included in a meta-analysis (Wolever & Mehling, 2003;Raatz et al, 2005;McMillan-Price et al, 2006;Bellisle et al, 2007;Sichieri et al, 2007;Abete et al, 2008;Jensen et al, 2008;Philippou et al, 2008;Philippou et al, 2009a;Philippou et al, 2009b). Two trials were subsequently identified in the update search Gogebakan et al, 2011) 10.16.…”
Section: Fasting Blood Lipids Fasting Total- Ldl- Hdl-cholesterol Amentioning
confidence: 99%
“…Four randomised controlled trials were identified that presented evidence on GI in relation to the ratio of fasting total cholesterol:HDL-cholesterol ratio, all of which were included in a meta-analysis (McMillan-Price et al, 2006;Bellisle et al, 2007;Philippou et al, 2008;Philippou et al, 2009b) Glycaemic index and fasting non-esterified fatty acid concentration…”
Section: Fasting Total Cholesterol:hdl-cholesterol Ratiomentioning
confidence: 99%